2005
DOI: 10.1371/journal.pbio.0030309
|View full text |Cite
|
Sign up to set email alerts
|

The Genomics of Disulfide Bonding and Protein Stabilization in Thermophiles

Abstract: Thermophilic organisms flourish in varied high-temperature environmental niches that are deadly to other organisms. Recently, genomic evidence has implicated a critical role for disulfide bonds in the structural stabilization of intracellular proteins from certain of these organisms, contrary to the conventional view that structural disulfide bonds are exclusively extracellular. Here both computational and structural data are presented to explore the occurrence of disulfide bonds as a protein-stabilization met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
137
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(143 citation statements)
references
References 51 publications
5
137
1
Order By: Relevance
“…They play important roles in a variety of functions, including metal binding and formation of disulphide bonds that alter protein structure. 18 For these reasons, mutations causing the appearance or loss of this residue are often pathogenic. Furthermore, the 296 location within the myocilin gene shows significant evolutionary conservation (UniProt database http://www.uniprot.org/) through to the Zebrafish species Danio rerio (data not presented).…”
Section: Discussionmentioning
confidence: 99%
“…They play important roles in a variety of functions, including metal binding and formation of disulphide bonds that alter protein structure. 18 For these reasons, mutations causing the appearance or loss of this residue are often pathogenic. Furthermore, the 296 location within the myocilin gene shows significant evolutionary conservation (UniProt database http://www.uniprot.org/) through to the Zebrafish species Danio rerio (data not presented).…”
Section: Discussionmentioning
confidence: 99%
“…A modification of this approach has been reported (4,59): by analyzing Cys a-carbons located within a distance of 8 Å from each other (C-C distance in Fig. 3), the majority (up to 80%) of disulfide bonds could be detected.…”
Section: Structural Disulfidesmentioning
confidence: 99%
“…As a result, the stabilizing mechanisms have been extensively explored for water-soluble proteins. The mechanisms observed include an increase in secondary structure propensity; 1,2 changes that decrease unfolded state entropy such as the introduction of Pro residues, reduction of Gly residues, 3 smaller loops, 4 and the addition of disulfide bonds; [5][6][7] an increase of hydrogen bonds and salt bridges; [8][9][10][11][12] and better optimized hydrophobicity. 13 Szilagyi and Zavodszky 3 made an extensive study of many protein families and found that few of these mechanisms were general, except an increase in salt bridges.…”
Section: Introductionmentioning
confidence: 99%